The man in the iron mask - Dumas, Alexandre, 1802-1870.; Rogers, Jacqueline (New York : Signet Classics, 2006)
In their final adventure, the four Musketeers plot to replace King Louis XIV of France with the mysterious, masked prisoner in the Bastille believed to be Louis' falsely imprisoned twin brother and the true king.
"Part three of the historical romance, Le Vicomte de Bragelonne, which is the last novel in the Alexandre Dumas' Musketeer cycle consisting of The Three Musketeers (1844) and Twenty Years After (1845)"--P. [xiii]
Includes bibliographical references (pages [496]-497).
Keywords: Man in the Iron Mask -- Fiction; France -- History -- Louis XIV, 1643-1715 -- Fiction; Historical fiction; Romances